Effects of nanoscale spatial inhomogeneity in strongly correlated systems - Silva, M. F.; Lima, N. A.; Malvezzi, André Luiz [UNESP]; Capelle, K. (Amer Physical Soc, 2005)
We calculate ground-state energies and density distributions of Hubbard superlattices characterized by periodic modulations of the on-site interaction and the on-site potential. Both density-matrix renormalization group and density-functional methods are employed and compared. We find that small variations in the on-site potential v(i) can simulate, cancel, or even overcompensate effects due to much larger variations in the on-site interaction U-i. Our findings highlight the importance of nanoscale spatial inhomogeneity in strongly correlated systems, and call for a reexamination of model calculations assuming spatial homogeneity.